Electronic and transport behavior of doped armchair silicene nanoribbons exhibiting negative differential resistance and its FET performance. Issue 21 (23rd February 2017) - Singh, Sukhbir; De Sarkar, Abir; Singh, Bijender; Kaur, Inderpreet
Abstract : The electronic and transport properties of armchair silicene nanoribbons (ASiNRs) doped with various elements are investigated. Abstract : In the present work, density functional theory (DFT) combined with non-equilibrium Green's function (NEGF) formalism is performed. The electronic properties (band structure and density of states) and transport properties (transmission spectrum and I – V characteristics) of armchair silicene nanoribbons (ASiNRs) doped with various elements, such as Al, Ga, In, Tl, P, As, Sb and Bi, are investigated. The negative differential resistance is observed for each doped ASiNR. The most geometrically stable structure and the maximum peak current to valley current ( I p / I v ) ratio is observed in indium (In) doped ASiNRs. Finally, In doped ASiNRs are proposed for field effect transistor (ASiNR-FET) formation using the high dielectric constant value of lanthanum oxide (La2 O3 = 29) at different applied gate voltages (−0.1 to 0.4 V). The In doped ASiNR device shows a negative differential resistance phenomenon, which can be controlled by an applied gate voltage. It is found that doping with In in the electrodes and scattering region provides a higher drain current, and higher I on / I off and I p / I v ratios. Our results have great application in digital devices and memory devices, and high frequency applications for future nanoelectronics.